Relationships among behavioural regulations, physical activity, and mental health pre- and during COVID–19 UK lockdown. (July 2021) - Bird, Jonathan M.; Karageorghis, Costas I.; Hamer, Mark
Abstract: A nationwide survey was conducted during the first UK lockdown to further understanding of the degree to which motives for exercise were associated with physical activity (PA) behaviours and, in turn, how PA behaviours were associated with mental health. A cross-sectional design was employed and data were collected by use of a one-off online survey ( N = 392; 18–85 years; M BMI = 25.48; SD BMI = 5.05; 314 women). Exercise motives, PA, and mental health were measured by use of the Behavioural Regulations in Exercise Questionnaire-3, Brunel Lifestyle Physical Activity Questionnaire, and General Health Questionnaire-12, respectively. Participants were also asked to specify their average step count per day, if they used a mobile device for this purpose ( n = 190). Analyses comprised hierarchical regressions and partial correlations. Results indicated that behavioural regulations were more strongly associated with planned PA pre-lockdown, compared to during lockdown. There were no differences observed in explained variance between pre- and during lockdown for unplanned PA and steps per day. Planned and unplanned PA were significant explanatory variables for mental health both pre- and during lockdown, but sedentary behaviour was not. Partial correlations, with BMI and age partialled out, showed that steps per day were not correlated with mental health either pre- or during lockdown. The range of variables used to explain planned and unplanned PA and mental health suggest that people's motives to exercise were tempered by lockdown. For those who routinely measured their steps per day, the step count was unrelated to their mental health scores both pre- and during lockdown. It appears that engagement in regular PA confers some minor benefits for mental health. Highlights: UK nationwide survey into physical activity (PA) behaviours and mental health. Exercise motives more strongly associated with planned PA pre-vs. during lockdown. Planned and unplanned PA explained mental health pre- and during lockdown. Sedentary behaviour not associated with mental health either pre- or during lockdown. Recommendations are provided for exercise-related interventions during lockdowns.